Arnold Chiari Malformations- A Short Review - Kumar, Voleti Vijaya; Ugandar, R. E.; Ismail, Y.; Delhiraj, N.; Pandiyan , P. Shanmuga; Ravi , M.; Chinababu, D.; Kiran, B. Hari; Hussain , N. Jawad; Sharma, K. Sai Shanmukha (Research Highlights in Disease and Health Research Vol. 3, 2023)
Chiari Malformation (Arnold-Chiari)-is a serious neurological disorder characterized by downward displacement the parts of cerebellum, where the bottom part of the brain, the cerebellum, fourth ventricle, pons and medulla oblongata into the spinal canal and putting pressure on both the brain and spine causing many symptoms. This is one of the causative factors of death in neonates and infants. Chairi malformations involve both skeletal and neural structures. Earlier it was estimated that the occurrence of chiari malformation is 1 in 1000 births but the occurrence of this condition was increased with the increased use of imaging techniques such as CT scans and MR imaging. However, it is very difficult to estimate the exact rate of occurrence as some of cases as asymptomatic or do not develop symptoms till adulthood. This review mainly focuses on thorough understanding of the direct and indirect sonographic findings, which are necessary for diagnosis of chiari II malformation in the developing fetus. The role of prenatal sonography in recognition of the malformation and prognostic value of these features are discussed.